The Parent Trauma Response Questionnaire (PTRQ): development and preliminary validation. Issue 1 (1st January 2018) - Williamson, Victoria; Hiller, Rachel M.; Meiser-Stedman, Richard; Creswell, Cathy; Dalgleish, Tim; Fearon, Pasco; Goodall, Ben; McKinnon, Anna; Smith, Patrick; Wright, Isobel; Halligan, Sarah L.
ABSTRACT: Background : Following a child's experience of trauma, parental response is thought to play an important role in either facilitating or hindering their psychological adjustment. However, the ability to investigate the role of parenting responses in the post-trauma period has been hampered by a lack of valid and reliable measures. Objectives : The aim of this study was to design, and provide a preliminary validation of, the Parent Trauma Response Questionnaire (PTRQ), a self-report measure of parental appraisals and support for children's coping, in the aftermath of child trauma. Methods : We administered an initial set of 78 items to 365 parents whose children, aged 2–19 years, had experienced a traumatic event. We conducted principal axis factoring and then assessed the validity of the reduced measure against a standardized general measure of parental overprotection and via the measure's association with child post-trauma mental health. Results : Factor analysis generated three factors assessing parental maladaptive appraisals: (i) permanent change/damage, (ii) preoccupation with child's vulnerability, and (iii) self-blame. In addition, five factors were identified that assess parental support for child coping: (i) behavioural avoidance, (ii) cognitive avoidance, (iii) overprotection, (iv) maintaining pre-trauma routines, and (v) approach coping. Good validity was evidenced against the measure of parental overprotection and child post-traumatic stress symptoms. Good test–retest reliability of the measure was also demonstrated. Conclusions : The PTRQ is a valid and reliable self-report assessment of parenting cognitions and coping in the aftermath of child trauma.